2021
DOI: 10.1007/s13762-021-03585-8
|View full text |Cite
|
Sign up to set email alerts
|

Effects of sewage sludge amendment and wetting–drying cycles of wastewater irrigation on structural improvement of clay soil

Abstract: Improving the structure of clay soils with sewage sludge to achieve better aeration and infiltration is one of the practical ways to maintain sustainable use of agricultural land. Furthermore, wetting-drying processes on the surface caused by changing irrigation intervals can supplement benefits to structural improvement under wastewater irrigation conditions. Therefore, a laboratory model study was carried out using three sewage sludge doses (50, 100, and 150 Mg ha −1 ), two types of water (freshwater, recycl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 32 publications
1
1
0
Order By: Relevance
“…The increase in W 33 agrees with that established by Turek et al (2019) for the addition of SCG in doses of 5%, 10%, 15% and 20%, attributing it to the changes in the OC contents in the soil. They also coincide with the results of Badaou and Sahin (2021) for the addition of sewage sludge (150 Mg ha −1 , corresponding to the addition of 2.5%). The tendency to increase the micro and mesoaggregates with the addition of SCG (Figure 3) could also be related to the increase in W 33 , since this water is more related to the structure than to granulometry (Rajkai et al, 2015).…”
Section: Discussionsupporting
confidence: 90%
“…The increase in W 33 agrees with that established by Turek et al (2019) for the addition of SCG in doses of 5%, 10%, 15% and 20%, attributing it to the changes in the OC contents in the soil. They also coincide with the results of Badaou and Sahin (2021) for the addition of sewage sludge (150 Mg ha −1 , corresponding to the addition of 2.5%). The tendency to increase the micro and mesoaggregates with the addition of SCG (Figure 3) could also be related to the increase in W 33 , since this water is more related to the structure than to granulometry (Rajkai et al, 2015).…”
Section: Discussionsupporting
confidence: 90%
“…Soil−groundwater interaction was a significant factor contributing to groundwater table variations, and the effect of irrigation induced the evolution of the seepage flow field in the model. 18,21,81 It was found that when these MPs were subjected to greater numbers of wet−dry cycles, the penetration depth of contaminants significantly increased, with an apparent linear relationship between depth and wet−dry cycle number. 77 Due to the continuous irrigation over 1 day in the model, there was a noticeable accumulation of water content in the irrigated area (5−10 and 15−20 m) with a global maximum seepage velocity of 5.786 × 10 −5 m/s, resulting in a rise in hydraulic head within the irrigated area (Figures S6 and S7).…”
Section: Quantitative Assessment Of Mp Migration In Variousmentioning
confidence: 99%
“…Based on the results obtained, the use of sewage sludge has caused the salinization of drainage water, which may pose a risk of salinization to the underlying groundwater. In a study conducted by A. N. Aboubacar Dan Badaou et al (2022), sewage sludge was used to improve soil structure, resulting in increased electrical conductivity in the drainage water.…”
Section: The Electrical Conductivity Of Drainage Watermentioning
confidence: 99%